Digital holography with self-imaging by a two-step phase element - Siemion, Agnieszka; Ducin, Izabela; Kakarenko, Karol; Makowski, Michał; Siemion, Andrzej; Suszek, Jarosław; Sypek, Maciej; Wojnowski, Dariusz; Kołodziejczyk, Andrzej (Photonics Letters of Poland, 2010)
The paper presents a method of recording digital holograms in a single shot by illuminating the photosensitive matrix with an especially structured reference beam formed by the Talbot effect from a periodical binary-phase diffractive element. This beam projects a 2D array of rectangular areas with different phase shifts. By interfering this beam with an object beam we achieve two phase shifted holograms which are then numerically reconstructed with a classical phase-shifting technique. The main advantage over a 4-step phase element is the easiness of fabrication and its alignment against the photosensitive matrix of a digital camera. Full Text: PDF References U. Schnars, W. Jüptner,"Direct recording of holograms by a CCD target and numerical reconstruction", App. Opt. 33, 179 (1994)[CrossRef] I. Yamaguchi and T. Zhang,"Phase-shifting digital holography", Opt.Lett. 22, 1268 (1997)[CrossRef] S. Lai, B. King, M. Neifeld,"Wave front reconstruction by means of phase-shifting digital in-line holography", Opt. Commun. 173, 155 (2000)[CrossRef] I. Yamaguchi, J. Kato, S. Ohta, J. Mizuno,"Image Formation in Phase-Shifting Digital Holography and Applications to Microscopy", App. Opt. 40, 6177 (2001)[CrossRef] A. Fajst, M. Sypek, M. Makowski, J. Suszek, A. Kolodziejczyk,"Self-imaging phase mask used in digital holography with phase-shifting", Proc. SPIE 7141, 714123 (2008)[CrossRef] A. Siemion, M. Sypek, M. Makowski, J. Suszek, A. Siemion, D.Wojnowski, A. Kolodziejczyk,"One-exposure phase-shifting digital holography based on the self-imaging effect", Opt. Eng. 49, 055802 (2010)[CrossRef] M. Sypek,"Light propagation in the Fresnel region. New numerical approach", Opt. Commun. 116, 43 (1995)[CrossRef] M. Sypek, C. Prokopowicz, and M. Górecki,"Image multiplying and high-frequency oscillations effects in the Fresnel region light propagation simulation", Opt. Eng. 42, 3158(2003)[CrossRef] Y. Awatsuji, A. Fujii, T. Kubota, O. Matoba,"Parallel three-step phase-shifting digital holography", Appl. Opt. 45, 2995(2006)[CrossRef] T. Nomura, S. Murata, E. Nitanai, T. Numata,"Phase-shifting digital holography with a phase difference between orthogonal polarizations", Appl. Opt. 45, 4873(2006)[CrossRef]